Wake up America [compact disc, unabridged] : the nine virtues that made our nation great-and why we need them more than ever - Bolling, Eric (Macmillan Audio, 2016)
Identifies nine values on which America was built--including manliness, profit, individuality, and religious faith--arguing that these values are under attack by Democratic leaders and must be embraced to revive the nation's dominance.